Integrating vibration sensing and non-speech visualization to notify hearing impaired students on fire in a controlled situation - Manaf, M.B.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
The existing fire and control measures in the market are particularly not effective when alerting the people with hearing impairment. The traditional alert systems such as flashing lights, smoke detector, beacons, strobes lights or even sign language with a one-to-one communication have proven to be not effective to address emergency situations. These alert systems do not communicate well with people having hearing impairment in directing them towards nearest exit points or accurately notify them of any alternative evacuation procedures. This paper presents a fire notification alert system which integrates non-speech visualization and vibration sensing techniques. Main goal is to achieve a higher level of alertness during fire in any controlled room. Each technique proposed is by considering elements embedded based on deaf preferences. Non-speech visualization is to produce notification in a glance by considering visual size display, color and functional issues. Vibration sensing on the other hand contains interpretable elements such as vibration size, frequency and modes. For this reason, display techniques undergo continuous experimentations in order to obtain the best alerting system designed for alarming the hearing impairs when fire took place. A series of empirical studies were conducted to analyze effectiveness of using these techniques especially in a controlled situation; which in this case, school kitchen workshop has been selected to test validity of integrating the two techniques. Hence, by using statistical analysis tool; integrating the two techniques is proven to increase the alert level of hard of hearing people. Â© 2015 IEEE.